Fatal Air Embolism after Choroidal Melanoma Endoresection without Air Infusion: A Case Report - Duangnate Rojanaporn (2022)
Background: The aim of this study was to report 2 cases of pulmonary air embolism developing several hours after choroidal melanoma endoresection without the use of air infusion during the surgery, with fatality in 1 patient. Methods: The method of this study was case report. Participants: Two patients with large choroidal melanomas who collapsed several hours after endoresection without air infusion as a result of pulmonary air embolism. Results: A 72-year-old man collapsed 4 h and 30 min after endoresection without air infusion. Computerized tomography angiography confirmed air embolism. The patient died after 86 min of cardiopulmonary resuscitation. A 41-year-old woman collapsed 5 h and 30 min after endoresection, performed without air infusion and with close monitoring, which included right internal jugular vein catheterization intraoperatively. Transthoracic and transesophageal echography, performed preoperatively, intraoperatively, and postoperatively, revealed air embolism only after collapse occurred. Imaging showed the embolism to be biventricular because of patent foramen ovale. The patient was treated promptly with extracorporeal membrane oxygenation and mechanical ventilation, which resulted in a full recovery. Conclusions: Air embolism can develop after endoresection for choroidal melanoma, despite avoiding air infusion. Further studies are needed to understand how this occurs. Special measures are indicated to detect this complication and to treat it promptly and effectively.